Neoplasias mamárias de cadelas: expressão gênica e proteica da via Wnt/b-catenina, sua associação com a transição epitélio-mesênquima e prognóstico - Terra, Erika Maria [UNESP] (2014)
Mammary tumors are very common in bitches and have a very similar biological behavior to the ones that occur in women, turning it an excellent model for comparative studies. Epithelial-mesenchymal transition (EMT) facilitate migration and the occurrence of metastasis, factor that have direct influence on prognosis. Thus, this study aimed to evaluate, by immunohistochemistry (IHC), EMT markers in canine mammary tumors (e-cadherin, β-catenin, vimentin and cytokeratin). In addition, gene and protein expressions of two genes WNT5A and APC were evaluated by qRT-PCR and immunohistochemistry. To this, 98 bitches with no breed or age predilection, besides normal mammary glands without neoplastic lesions were used to form four groups: (G1) 5 normal mammary samples; (G2) 28 benign mammary lesions; (G3) 56 non-metastatic mammary carcinomas and (G4) 14 metastatic carcinomas. Both genes, APC and WNT5A show higher expression between normal mammary samples and no difference among benign and malignant tumors (metastatic and non-metastatic). EMT phenotype was identified by multivariate analysis, because benign tumors were stongly associated with membranous β-catenin, high scores of Cytokeratin and no vimentin expression in epithelial cells and metastatic carcinomas were strongly associated to nuclear β-catenin, low E-cadherin expression and vimentin positivity in neoplastic epithelial cells. As nuclear localization of β-catenin is characteristic of Wnt/β-catenin signaling pathway aberrant activation, we can conclude that Wnt/β-catenin signalling pathway is activated among canine mammary tumors and EMT is occuring since benign epithelial cells have been transformed in mesenchymal cells in metastatic tumors. Those findings provide data for a better understanding of cancer progression and open new perspectives about research not only in mammary tumors, but also in other neoplastic types in dogs, facilitating to identify new prognostic factors and ...